THE EFFECTIVENESS OF EDUCATIONAL VIDEOS IN PREVENTING PREMARITAL SEXUAL BEHAVIOR AMONG GENERATION Z IN SOUTH JAKARTA - Zeni Zaenal Mutaqin; Fitrah Ivana Paisal; Husnul Khatimah (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
Premarital sexual relations have a negative impact on adolescents, namely the risk of sexually transmitted diseases, unwanted pregnancies, illegal abortions, and psychological trauma. This study aims to examine the effectiveness of educational videos in preventing premarital sexual behavior in generation Z. Researchers make educational videos and then measure their effect on increasing knowledge and attitudes. The research method is quasi-experimental. The population is grade 12 students at Vocational High School Al-Hidayah, South Jakarta. Samples were taken randomly. The intervention group was given educational video shows. The control group was given oral counseling. The result is that the educational video intervention affects increasing respondents' knowledge. As for the attitude has no effect. Educational videos need to be developed to increase the knowledge of teenagers as Generation Z who are very familiar with visual displays through cell phones that are used almost all the time by Generation Z.